2016
DOI: 10.7554/elife.14601
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer natural product ophiobolin A induces cytotoxicity by covalent modification of phosphatidylethanolamine

Abstract: Phenotypic screens allow the identification of small molecules with promising anticancer activity, but the difficulty in characterizing the mechanism of action of these compounds in human cells often undermines their value as drug leads. Here, we used a loss-of-function genetic screen in human haploid KBM7 cells to discover the mechanism of action of the anticancer natural product ophiobolin A (OPA). We found that genetic inactivation of de novo synthesis of phosphatidylethanolamine (PE) mitigates OPA cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 64 publications
1
50
0
1
Order By: Relevance
“…Disorders in PE metabolism have been implicated in many chronic diseases, such as Alzheimer's disease, Parkinson's disease, and nonalcoholic liver disease [82], as well as metabolic disorders such as atherosclerosis, insulin resistance, and obesity [63]. Increased levels of PE have been described in cancer cells leading to PE being regarded as a target in the development of anticancer therapies [83].…”
Section: Phosphatidylethanolamine and Its Physiological Functionsmentioning
confidence: 99%
“…Disorders in PE metabolism have been implicated in many chronic diseases, such as Alzheimer's disease, Parkinson's disease, and nonalcoholic liver disease [82], as well as metabolic disorders such as atherosclerosis, insulin resistance, and obesity [63]. Increased levels of PE have been described in cancer cells leading to PE being regarded as a target in the development of anticancer therapies [83].…”
Section: Phosphatidylethanolamine and Its Physiological Functionsmentioning
confidence: 99%
“…Natural products represent a rich source for small molecule therapeutics; however, the molecular targets of these compounds are often elusive. [45][46][47][48] CWO presents challenges for identifying the precise molecular target due to the complexity of the admixture and potentially combinatorial effects of the terpene constituents. CWO stimulated calcium signaling in keratinocytes, followed by NFAT translocation to the nucleus ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that a natural product, ophiobolin A (OPA) exerts its cytotoxicity toward cancer cells by forming a pyrrole-containing covalent cytotoxic adduct with the ethanolamine head group of PE, subsequently leading to lipid bilayer destabilization (Chidley et al, 2016). OPA is a plant toxin isolated from pathogenic fungi of the Bipolaris genus that exhibits cytotoxicity at nanomolar concentrations against a range of cancer cell lines.…”
Section: Phosphatidylethanolamine As An Anti-cancer Targetmentioning
confidence: 99%
“…OPA is a plant toxin isolated from pathogenic fungi of the Bipolaris genus that exhibits cytotoxicity at nanomolar concentrations against a range of cancer cell lines. Basically, the study performed an unbiased genome-wide approach to identify the molecular target of OPA through insertional mutagenesis of near-haploid cell line KBM7 using retroviral gene trap approach and demonstrated that OPA forms PE-OPA adducts associated with membrane disruption and eventual cell death (Chidley et al, 2016). This discovery highlighted the potential importance of PE as the molecular target for small molecules which provides further impetus to pursue targeting PE as a novel chemotherapeutic approach, particularly against cancer types which are known to respond poorly to current chemotherapy.…”
Section: Phosphatidylethanolamine As An Anti-cancer Targetmentioning
confidence: 99%